Website Development of Enterprise ERP Based on Construction Industry - Mahajan, Bhushan (Journal of Advance Research in Computer Science & Engineering (ISSN 2456-3552), 2015)
With the fast development of the information technology and enterprise business, the traditional desktop management system based on three-tier architecture could not satisfy the need of enterprises. In this project we develop a website for construction industry for a new solution of enterprises ERP which is based on construction field.